MicroRNAs as New Biomarkers for Diagnosis and Prognosis, and as Potential Therapeutic Targets in Acute Myeloid Leukemia - Trino, Stefania (Int J Mol Sci, 2018)
Acute myeloid leukemias (AML) are clonal disorders of hematopoietic progenitor cells which are characterized by relevant heterogeneity in terms of phenotypic, genotypic, and clinical features. Among the genetic aberrations that control disease development there are microRNAs (miRNAs). miRNAs are small non-coding RNAs that regulate, at post-transcriptional level, translation and stability of mRNAs. It is now established that deregulated miRNA expression is a prominent feature in AML. Functional studies have shown that miRNAs play an important role in AML pathogenesis and miRNA expression signatures are associated with chemotherapy response and clinical outcome. In this review we summarized miRNA signature in AML with different cytogenetic, molecular and clinical characteristics. Moreover, we reviewed the miRNA regulatory network in AML pathogenesis and we discussed the potential use of cellular and circulating miRNAs as biomarkers for diagnosis and prognosis and as therapeutic targets.